A new insular, endemic frog of the genus Kalophrynus Tschudi, 1838 (Anura: Microhylidae) from Tioman Island, Pahang, Peninsular MalaysiaDepartment of Biology, La Sierra University, 4500 Riverwalk Parkway, Riverside, California, 92515-8247 USA. - Onn, Chan Kin; Grismer, L. Lee; Grismer, Jesse (Zootaxa, 2011)
A new insular, endemic species of microhylid frog of the genus Kalophrynus is described from Tioman Island, off the southeastern coast of Pahang, Peninsular Malaysia. Kalophrynus tiomanensis sp nov. can be differentiated from its congeners by the following combination of characters: SVL 21.4–26.3 mm; reduced webbing on toes; outer metatarsal tubercle absent; large, black inguinal spot and unique markings on dorsum. This discovery increases the number of endemic species of amphibians on Tioman Island to at least three.